Exploring The Correlation Between Chemical Abstraction Ability and Student Learning Outcomes :A Quantitative Analysis in High School Chemistry Learning - Kurniawati, Yenni; Dongoran, Rahmita Murdiati; Utami, Fitri Tri; Novia, Efrida (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2025)
Chemical abstraction ability is an important thing to analyze because it is closely related to the cognitive style of students. This ability is suspected as an ability that affects learning achievement. This study aims to obtain information about the correlation between the ability of chemical abstraction with student learning achievement on Chemical Bonding material in class XI IPA 2 SMAN 2 Kampar. This research is a correlation research using descriptive quantitative method. Purposive sampling technique was used in this study. A total of 23 students of class XI IPA 2 were sampled in this study. Observation sheets, subjective tests in the form of essay tests, interviews related to students' chemical abstraction abilities are instruments in this study. The results showed that there is a significant relationship between the ability of chemical abstraction with student learning achievement on the material of Chemical Bonding in class XI IPA 2 SMAN 2 Kampar. This can be seen from the rxy which is greater than the rtable at a significant level of 5% and 1% with df n-2 (0.708 > 0.433 and 0.708 > 0.549). Ha is accepted and H0 is rejected. The results of this study indicate that students' chemical abstraction ability is in the low category, so further research needs to be done to improve students' chemical abstraction ability and learning achievement.